The royal tutor. 13 - Akai, Higasa (Yen Press, 2020)
"Dismayed by the disturbance at Cafe Mitter Meyer, Prince Licht is keen to investigate--but it seems his urgency may throw him under his coworker's suspicions... Licht faces a choice: hide or be revealed? Hinder or help? What lesson can Heine pull from Licht's turmoil?"--Provided by publisher.